Status of the Separated State Assets into BUMN Persero - Ghora Putra Bafelanna (Faculty of Law, University of Mataram, 2020)
The regulation of the status of state finances in the State owned enterprise (BUMN) environment in the BUMN Law and the Law on State Finance shows that there is a very significant difference in the status of state separated state assets from BUMN. The applied problem approach in this legal research is statutes approach. The Principle of State Assets Separation in the form of Equity Participation in Persero is also supported by the existence of a Fatwa from the Supreme Court Number WKMA / Yud / 20 / VIII / 2006 concerning the Separation of BUMN assets from state assets. The contents of the fatwa are related to Article 1 number 1 of the BUMN Law and Article 4 paragraph (1) of the BUMN Law which, according to the Supreme Court, is a more specific law concerning BUMN, it is clearly said that enterprises’ capital which originating from separated state’s earning and expenses shall be based on the principles of a sound corporate.